Public Libraries Regional Seminars 2006-2012: An Evaluation of In-service Training Model in Turkey - Bülent Yılmaz (Türk Kütüphaneciliği)
In this study, a general evaluation of the serials called Public Libraries Regional Seminars practiced as an authentic in-service training model between the years of 2006-2012 in Turkey has been made. According to this, 20 Regional Seminars which were practiced based on cooperation of formal-civil institutions in 18 different provinces and 1 county with 782 participants and almost 100 speakers in 6 years has been determined to have crucial contributions to the history of Turkish public librarianship.